P01.097 Subclassification of low-grade gliomas considering TERT promoter mutation and ATRX loss: beyond the 2016 WHO classification. (19th September 2018) - Roh, T; Kang, S; Kim, E; Moon, J; Hong, C; Chang, J
Abstract: Background: Grade II glioma is a heterogeneous group of various pathologies. 2016 WHO classification defined subgroups of Grade II gliomas based on isocitrate dehydrogenase (IDH) mutation and 1p/19q codeletion status. However, implications of telomerase reverse transcriptase promoter ( TERT p) mutation and alpha-thalassemia/mental retardation syndrome X-linked (ATRX) loss are not considered in the classification. Material and Methods: Patients ( n = 191) who underwent surgery and pathologically proven for supratentorial newly diagnosed low-grade glioma (WHO grade II) were included this study. Molecular diagnoses including IDH1/2 mutation, 1p/19q codeletion, TERT p mutation, ATRX expression, O 6 -methylguanine-DNA methyltransferase ( MGMT ) promoter methylation status was evaluated. The overall survival according to TERT p mutation and ATRX loss in each 2016 WHO class were compared. Results: There were 34 (17.8%) IDH-wildtype astrocytomas, 81 (42.4%) IDH-mutant astrocytomas, and 76 (39.8%) IDH-mutant and 1p/19q-codeleted oligodendrogliomas. The median overall survival (OS) of each group were 3.9, 10.4, and 18.7 years, respectively. TERT p mutation had negative impact for survival in IDH-wildtype astrocytomas (HR = 5.458, 95% confidence interval [CI] 1.771–16.826), while no significant differences were observed regarding TERT p mutation in IDH-mutant astrocytomas and oligodendrogliomas. Among IDH-wildtype/TERTp-mutant astrocytomas, ATRX loss was significantly correlated with poor outcome (2.1 vs 3.0 years, p=0.033). Conclusion: Molecular status of TERT p mutation and ATRX expression can be integrated into the 2016 WHO classification of low-grade gliomas. TERT p mutation has the reciprocal implication depending on the presence of IDH mutation in astrocytomas. IDH-wildtype astrocytomas which harbor TERTp mutation only without ATRX loss showed the worst prognosis which is comparable to glioblastomas. Low-grade glioma is a collection of heterogeneous tumors and needs more segmentation.